ПРОБЛЕМИ ВАЛЮТНО-ФІНАНСОВОЇ КОНВЕРГЕНЦІЇ В ЄС - Йодко, Мірослав (Науковий журнал «Світ фінансів», 2017)
Йодко М. Проблеми валютно-фінансової конвергенції в ЄС. Висвітлено практичні питання десятилітнього функціонування території зони євро. Представлено загальну оцінку впливу спільної валюти на європейську економіку. Проведено порівняльний аналіз економічного розвитку країн зони євро та інших країн ЄС. Окреслено перспективи розвитку території зони євро. Yodko M. Problems of currency-financial convergence in EU. Practical issues of the ten ears functioning of euro zone are consider. The overall assessment of the impact of the common currency of the European economy are presented. Comparative analysis of the economic development of the euro zone and other countries of European Union is carried out. The prospects for the development of the euro zone are described.